The impact of the urban–rural residents’ medical insurance integration on rural residents’ out-of-pocket medical costs: based on the deductible, reimbursement rate, and ceiling line - Liu, Chen; Kong, Yue; Su, Qun; Xing, Huaizhen; Tian, Zhongbao (Frontiers in Public Health, 2025)
BackgroundAfter China implemented the Urban and Rural Residents’ Basic Medical Insurance (URRBMI) integration reform in 2016, medical costs for rural residents remain unalleviated. This might be attributed to the program’s higher deductibles, combined with lower reimbursement rates and ceiling lines.MethodsUsing CHARLS data from 2013 - 2020, this study employs a two-stage Heckman model to examine the impact of changes in deductibles, reimbursement rates, and ceiling lines in the URRBMI reform on out-of-pocket (OOP) medical costs for rural residents. A fixed-effects DID model is also utilized for robustness testing.Results(1) Lowering the deductibles for outpatient visits and increasing the outpatient reimbursement rates and ceiling lines can significantly unleash the demand for outpatient visits. The key to reducing residents’ OOP outpatient costs lies in lowering the deductibles and ceiling lines. Meanwhile, the current increase in URRBMI reimbursement levels has not enhanced rural residents’ willingness to seek inpatient visits, and rural residents’ OOP inpatient cost is more sensitive to the inpatient reimbursement rate. (2) Increasing the reimbursement level is conducive to releasing the medical demand of vulnerable groups, such as rural low-income groups and those with poorer health, and is also crucial for reducing the medical burden. The medical behaviours of rural middle-and high-income groups are less influenced by the reimbursement level.ConclusionThe policy design of medical insurance should give priority to the following: (1) reducing the financial burden of vulnerable groups by lowering deductibles and raising reimbursement ceilings; (2) expanding coverage for major diseases; and (3) expanding the catalogue of reimbursable medicines. These findings offer valuable insights for healthcare reform in developing countries.